2016
DOI: 10.3329/ralf.v3i1.27878
|View full text |Cite
|
Sign up to set email alerts
|

Study on marketing channel and value chain analysis of some commercially important marine fish species available in Cox’s bazar area, Bangladesh

Abstract: A study was conducted to investigate marketing channel and value chain analysis of some commercially important marine fish species available in Cox’s Bazar area, Bangladesh. Three commercially important marine fish species were investigated in respect to their marketing channel and value analysis: 1) Pomfret, Stromateus chinensis, 2) Jewfish, Otolithoides argenteus and 3) Hilsha, Tenualosa ilisha. Three marketing channels mainly encompasses from fishermen to consumers, namely the primary, secondary and retail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…1300/ kg. Ahsan et al (2016) reported that four marketing chains were found for pomfret fish marketing. In marketing chain I, pomfret fish reached the export market from fishermen through a landing centre, depot and processing plant.…”
Section: Resultsmentioning
confidence: 99%
“…1300/ kg. Ahsan et al (2016) reported that four marketing chains were found for pomfret fish marketing. In marketing chain I, pomfret fish reached the export market from fishermen through a landing centre, depot and processing plant.…”
Section: Resultsmentioning
confidence: 99%